Transforming industrial manipulators via kinesthetic guidance for automated inspection of complex geometries - Loukas, Charalampos; Vasilev, Momchil; Zimmerman, Rastislav; Vithanage, Randika K. W.; Mohseni, Ehsan; MacLeod, Charles N.; Lines, David; Pierce, Stephen Gareth; Williams, Stewart; Ding, Jialuo; Burnham, Kenneth; Sibson, Jim; et al. (MDPI, 2023)
The increased demand for cost-efficient manufacturing and metrology inspection solutions for complex-shaped components in High-Value Manufacturing (HVM) sectors requires increased production throughput and precision. This drives the integration of automated robotic solutions. However, the current manipulators utilizing traditional programming approaches demand specialized robotic programming knowledge and make it challenging to generate complex paths and adapt easily to unique specifications per component, resulting in an inflexible and cumbersome teaching process. Therefore, this body of work proposes a novel software system to realize kinesthetic guidance for path planning in real-time intervals at 250 Hz, utilizing an external off-the-shelf force–torque (FT) sensor. The proposed work is demonstrated on a 500 mm2 near-net-shaped Wire–Arc Additive Manufacturing (WAAM) complex component with embedded defects by teaching the inspection path for defect detection with a standard industrial robotic manipulator in a collaborative fashion and adaptively generating the kinematics resulting in the uniform coupling of ultrasound inspection. The utilized method proves superior in performance and speed, accelerating the programming time using online and offline approaches by an estimate of 88% to 98%. The proposed work is a unique development, retrofitting current industrial manipulators into collaborative entities, securing human job resources, and achieving flexible production.
Keywords: collaborative robotics; non-destructive evaluation; WAAM; kinesthetic; robot programming